Stadsförtätningens teorier och konsekvenser : Analys av kvaliteter och förtätningspotential för Luleå centrum - Arnehed, Sebastian; Emilsson, Henrik (2011)
Urban densification has for many years been the common norm for achieving the sustainable city. The current debate, appearing in the literature review is focused on how urban sprawl could be stopped and how cities instead will be planned with sustainability as the ground ideal. But what are the reasons for the belief that the dense city is the same as the ecologically, economically and socially sustainable city? The aim of this study is partially to clarify the current debate within the research area and to make an effort to apply the theories to the city centre peninsula of Luleå. The aim is to encourage the dialogue and the discussion about urban densification in Luleå.The literature review deals with a diversity of factors related to densification, such as travelling distance, energy consumption, noise pollution, social sustainability among others. The dense city presents a number of advantages based on the literature review, such as reduced consumption of energy per inhabitant and shorter travelling distance. These studies, previously mainly done on international larger cities, have also been proved to be true for smaller Scandinavian cities. A correlation that previously has been questioned. That the dense city is the same as a city without access to green space is described in several studies as a misunderstanding. In dense urban environments, high quality green spaces can compensate quantity. Several studies show that it is quality and not quantity that determines how people perceive the availability of good urban spaces. A majority of the literature also says that the social life within the city is strengthened with an increased density. There is however some disagreement that the planning has to take into consideration, including the risk of an increasing segregation when new development occurs at high value land.The literature review concludes that urban densification contributes to a sustainable development. Urban densification is also based on changes in the existing city structure, a structure that ...